PELATIHAN TEKNOLOGI BUDIDAYA AQUAPONIK UNTUK MENINGKATKAN EKONOMI DAN KETAHANAN PANGAN MASYARAKAT DESA TARABAN BREBES - Nota Ali Sukarno Nota; Afif Hendri Putranto; Siska Irma Budianti; Ferdian Yudha Fariezki; Rifqi Efendi; Putri Olivia Nurman; Slamet Wiarso; Julianto Ibnu Natan (Perwira Journal of Community Development, 2026)
Aquaponics is one form of urban farming, alongside hydroponics. Aquaponics also serves as a solution for food security and economic improvement for communities with limited land. In this community service program, training on aquaponics cultivation technology on limited land was carried out to improve the economy and food security of the residents of Taraban Village, Paguyangan District, Brebes Regency. Taraban Village was chosen as the location for this community service due to limited land availability, the need for economic improvement, strengthening food security, and the community's familiarity with farming. The aim of this training is to teach how to cultivate plants using the aquaponics system to enhance family income and fulfill food needs with limited land. The methods used in this community service activity include socialization, training, provision of tools, mentoring, and evaluation of plant cultivation using aquaponics technology. The training was attended by 31 participants and was held on August 10, 2025, at the Taraban Village Hall. The results achieved are a series of methods, namely the partners learned about how to cultivate plants, the partners were also able to directly practice plant cultivation using aquaponic technology, the partners could experience food sufficiency, namely plant and animal protein free from chemicals, and it can improve family economy. The types of plants cultivated are mustard greens, water spinach, and bok choy, as well as catfish. As for the participants who have been able to create an aquaponic system, it is 65% of the participants who attended the training.